Effect of Bamboo Node for Construction Application - Widodo, Akhmad Basuki; Panunggal, Eko; Widjaja, Sjarief; Rasyid, Daniel M.; Soegiono (IPTEK The Journal for Technology and Science, 2025)
In use of material for structure application, the most critical shares is jointed area, where this area is accumulation of stress accepted from existing burden. In structure laminate, joints represent part of drawback from the construction. And so do that happened at node in bamboo. Every part of bamboo there are node and internode. strength of bamboo with the internode will be downhill 25 % compared to bamboo without internode. In this research aim to know effect of bamboo node in construction laminate. Examination of test made with lamination without node and by node. Examination covering test of static bending and tensile strength. Standard used ASTM D-143. From result of examination and analyse, indicating that there difference between strength of wood laminate with internode and wood laminate without internode. But degradation of strength not equal to difference of strength of bamboo solid. At bamboo composite of degradation of strength only equal to 4.88 %, while wood and bamboo composites, where part of bamboo one-third from composite, degradation of strength reach 18.33 %. But degradation of the strength still fulfill conditions for structural used.